Análisis Comparativo del desempeño en el Marco del GEM Global Entrepreneurship Monitor del sector de comidas rápidas y su contribución en la generación de Emprendimientos en la ciudad de Guaranda en el año 2018 - Gavilanez Ibarra, Richar Fernando (2019)
During recent years in the city of Guaranda has been observed the growth of new ventures, the fast food sector has been gaining market, because of this arises the research project itself based on an innovative methodology seeks to define those elements described by this sector, based on the objectives of the methodology, such as: measuring the level of entrepreneurial activity, analyzing factors and identifying areas of opportunity that make it possible to improve entrepreneurial activity, in order to raise awareness of the relevance of the ventures in the city of Guaranda, characterizing the entrepreneurs, being able to define those factors of greater incidence at the time of deciding to undertake in the same way to publicize the reasons for which people have incurred in starting up this type of ideas, the jobs that have been propitiated and the economic movement that it generates, being necessary to be able to achieve this, follow a methodology to establish a descriptive - retrospective study which will expose all those singularities of the activity, due to the source from which the data is obtained, this is of a documentary type given that initially information is sought to allow knowing the object of study such as: what is the GEM, what are the theories of entrepreneurship, objectives of the venture, types, among other topics exposed in the frame of reference, considering also field because the data is obtained from the owners of the business for which the investigators move to where they are located, the population that was considered were the premises registered in the Internal Revenue Service (SRI) with the activity "Fast food restaurants, refreshment stands and establishments that offer take-away, pizza delivery , etc; ice cream shops, soda fountains, etc. "ascending to 63 stores from which a sample of 55 establishments is obtained, with the result that the most representative dichotomous characteristics is the female sex, with an average age of 30 to 49 years, where the The predominant polytomous characteristic is that the entrepreneurs present a secondary level of education, who started the business driven by the need, determined that the most influential factors that impede or make it possible to start an idea are the sources of financing, the little education in entrepreneurship, scarce sources of work, family support among other aspects that are detailed in the results of the intervention action, but despite this have been able to arise with their establishments and today have been able to employ an average of 57 people , generating an economic movement of $ 17,807 per month, with a return of $ 30. 920.5. Descriptive Terms: fast foods, Guaranda, entrepreneurship, GEM, economic performance, jobs